Soybean molasses for biogas production in an upscale and cost-effective anaerobic reactor: Insights in metagenomic and metabolic pathways - de Mello, Bruna Sampaio [UNESP]; Motteran, Fabricio; Rodrigues, Brenda Clara Gomes [UNESP]; dos Santos, Alex Valerio; Thomaz, Daniel; Sarti, Arnaldo [UNESP] (Elsevier, 2025)
Lab-scale studies have successfully demonstrated the potential of soybean molasses as substrate for anaerobic digestion and biogas production. In this context, this study performed the scale up of the biogas production from soybean molasses using 1.2 m³ pilot-scale anaerobic semi-batch reactor focusing on the development of a cost-effective process for implementation in soybean processing industries. The reactor performance was evaluated by varying the amount of soybean molasses fed to the reactor and the duration of the feeding cycles. Biogas yield of 350 L d−1 as well as cumulative biogas production and specific methane production of 3.6 m³ and 50.5 LCH4 kgVS−1 d−1, respectively, were reached by adding 5 L of soybean molasses for a time cycle of 8 days. In addition, microbial analysis revealed that the most abundant genera involved on soybean molasses biodegradation were Enterococcus, Lachnoclostridium, Eubacterium and Klebsiella for bacteria domain with relative abundance of 13.8, 10.1, 9.5 and 5.6 %, respectively. The inoculum demonstrated an integrated microbial community capable of sustaining methanogenesis, which dominant genera within archaea domain were Methanosarcina and Methanoculleus. Overall, although glucose was the main substrate metabolized, the substrate composition directly influenced the activated microbial metabolic pathways. The microbiome showed higher expression of genes related to direct intracellular conversion, reflecting the higher availability of simple sugars present in the soybean molasses. Moreover, despite lower methanogenic taxonomic diversity, the main KOs associated with methanogenesis were more abundant feeding with soybean molasses compared to the initial inoculum.